Abruptio placentae is a clinical manifestation of severe vascular disease in pregnancy - Pacora, Percy (2015)
To determine the prevalence and risk factors of placental abruption (DPP). MATERIALS AND METHODS: l) of January 1, 1980 to December 31: A study retrospectioo DPP all cases that occurred in the National Teacher San Bartolomé Mother-Child Hospital in Lima for 19 years, was conducted in two periods 1989; 2) l January 1991 to December 31, 1999, a retrospective analysis of the perinatal information DPP cases registered in the Perinatal Information System (SIP) of the hospital was performed. DPP diagnosis was performed by macroscopic visualization of a blood clot in the maternal face of the placenta inserted into the upper uterine segment. RESULTS: The DPP occurred in 0.4% of pregnancies (464/107 854). Risk factors associated with the DPP were: genetic and / or hereditary (poor reproductive history: previous stillbirth 28% (129/464), preterm delivery before 9% (26/284)); emotional (multiparity 74% (296/462) after fetal death 9% (26/284)); social (lack of prenatal care 71% [329/464], low education level of 11% [19/180]); nutritional, vascular and metabolic (maternal malnutrition 28% [47 / 169J, older than 30 years 27% [122/459], preeclampsia-eclampsia 25% [116/464], vaginal bleeding blood vessel disease or uteroplacental choriodecidual 100% [ 100/100], anemia 26% [46/180], perinatal asphyxia 33% [154/464], fetal malnutrition / low birth weight 44% [153/348]); anatomical (preterm premature rupture of membranes 4% [5/119], anatomic congenital defect 3% [5/156]); and infectious (fetal infection and neonatal sepsis 8% [13/156], puerperal infection 3% [15/464]). No association with twin pregnancy, fetal male sex, smoking, and use of illicit drugs was found. CONCLUSIONS: The DPP is the manifestation of a severe vascular disease whose origin is multifactorial and occurred in 0.4% of pregnancies in women of Lima. The DPP is associated with increased maternal / perinatal morbidity, premature birth and perinatal mortality.